Ideological Fantasy of Social Harmony (Rukun) in Rural Java, Indonesia, in Ahmad Tohari’s Di Kaki Bukit Cibalak - Uluwwi, Muhammad Ulul; Harjito, Harjito; Septiana, Ika (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Ahmad Tohari presents the narrative of a village community under a corrupt village head in the novel Di Kaki Bukit Cibalak (2022). One of the villagers initiates an effort to improve the village's economic state amid hesitation to confront the corrupt village head. This article qualitatively examined the ideological fantasy of social harmony (rukun) in rural Java, Indonesia, as depicted in Ahmad Tohari's Di Kaki Bukit Cibalak. The sociology of literature approach correlated the story's facts with the social realities in Java. Data were collected through documentation techniques. Meanwhile, the analysis was conducted using Slavoj Žižek's theory of ideological fantasy and the concept of social harmony. The findings revealed that the lower-class villagers in rural Java had a symbolic mandate to 'surrender' to maintain social harmony, even though the subject aimed to defy the corrupt village head. The Javanese villagers preferred to avoid open conflict, which led the subject to leave its idealism rather than confront the corrupt leader despite their disgust of the corruption and their aspiration to improve the village. As the representation of reality, it is critical as the ideological fantasy of social harmony causes the lower-class villagers to postpone resisting the corrupt village head to maintain peace, providing chances for any kind of violences thrive in real life.